Dutch sustainable schools towards energy positive. (September 2018) - Golshan, Milad; Thoen, Hester; Zeiler, Wim
Abstract: Due to the effects of Global warming, the Built Environment needs to become more sustainable and use less energy. This means that also schools have to become energy neutral of even energy positive. Classrooms are considered to be very important for children's mental and educational development. On average, kids spend over 30% of their time in classrooms in the pursuit of their academic goals. Therefore, great care must be taken to ensure the learning environment for kids is comfortable, vibrant and healthy. This paper aims to evaluate the indoor environmental conditions of 10 energy conscious schools in the Netherlands ranked amongst the top 15 efficient schools in the Netherlands in 2016. For evaluation of the environmental conditions in schools, focus was placed on the thermal comfort and indoor air quality (IAQ) conditions. The results from the study indicates that the situation is less than desirable in some cases and the focus had been placed mostly on energy aspect rather than comfort or healthy indoor environment of the occupants. Highlights: 10 of the most efficient Dutch schools have been evaluated on designed energy consumption and IAQ. Most school projects focused on energy efficiency rather than improved IAQ. In most schools the ventilation perceived insufficient even though advanced ventilation systems were installed. Half of the schools had students complaining about Sick Building Symptoms. It is in practice difficult to achieve low energy consumption and at the same time high IAQ.